EVALUATION OF EFFICACY AND SAFETY OF DIACEREIN IN OSTEOARTHRITIS OF KNEE JOINT - DILIP KUMAR RENAPURKAR,; SHOBANA MATHUR,; K.L. JAGDISHWER RAO, (International Journal of Pharma and Bio Sciences, 2010)
Back Ground : Diacerein, a New Drug for Osteoarthritis has already been in the market for last two years. This study is a post marketing survey of the drug Diacerein. The Aims of this study are: Primary Objectives: 1. To evaluate efficacy of Diacerein 2. To monitor adverse drug reaction. Secondary Objectives: To know whether Diacerein brings about functional as well as structural improvement in osteoarthritis of knee joint. Study Design & Methods: 120 male and female patients who were capable of giving written informed consent within an age range of 30 years to 80 years were selected. The study was done at Princess Esra Hospital affiliated to Deccan College of Medical Sciences, Hyderabad. Diacerein 50 mg tab was administered orally once daily to them for period of four months. Ethical committee approval and patient consents were obtained prior to the beginning of the trial. Ambulatory non pregnant females and males 30 to 80 years of age were included. Subjects are made to withdraw all NSAIDs except Diacerein. Severe Chronic cases in elderly debilitated patients were not included. Treatment Safety / Efficacy study phase IV Eligibility criteria. The patients were studied by 1986 criteria laid down by American College of Rheumatism. Findings : Out of the 120 cases seen for the period of four months all of them improved on the pain scale. No adverse effects were seen on Noranjo Scale. Improvements seen on the X-ray images were the characteristic findings. Interpretation : We can conclude from the results that Diacerein is very useful, disease modifying drug for Osteoarthritic patients bringing about structural and functional changes in the joints of OA patients with less adverse effects.